USING E-CATALOG SYSTEM TO REDUCE COST IN PROCUREMENT OF DRUGS - Suliantoro, Hery; Permatsari, Eldinda Sazida; Handayani, Naniek Utami (J@ti Undip : Jurnal Teknik Industri, 2016)
The price of drugs in Indonesia is still relatively expensive in both the government and private sectors. A survey conducted in 2004 showed that the price of patented drugs in Indonesia is 22 to 26 times higher than the International Reference Price (IRP). As for generic drugs, though cheaper than patented drugs, the price is still nine times higher than the IRP. To overcome these problems, the government facilitated the procurement of generic drugs by using the e-Catalog. But not all hospitals can purchases drugs through the e-Catalog, some still use the conventional methods to supply the needs of medicine where the prices are more expensive than the prices of the e-Catalog. The case studies carry out in one of private hospital, and selection of items examined using Kraljic Portfolio Matrix. After doing research, the selected item that is on strategic items is Omeprazole. The price difference is due to different contract system. In the conventional way, the contract made between the Hospital and the main distributor. While, Â the e-Catalog way, contracts made directly to the pharmaceutical factory through the framework contract with government (LKPP). In the future, the conventional way must be abandoned, because through the e-Catalog, procurement is more efficient, thereby reducing time and costs